International Operations Networks 2014
DOI: 10.1007/978-1-4471-5646-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Changing Roles of Western Subsidiaries in China: Balancing Global Priorities with Local Demands

Abstract: Over the past 30 years of economic development, the role of subsidiaries in China has changed. China has become an important host country for subsidiaries of western multinational companies seeking cost advantages and/or access to the emerging market potential. The objective of this paper is to explore the effects of the emerging strategic mandate of subsidiaries to serve local demands while meeting global corporate standards and operations priorities. We confirm well established dimensions such as strategic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…By contrast, it has been shown that subsidiaries are strategically expansive, i.e. the role of offshored sites is likely to be upgraded and could entail new capabilities (Adeyemi et al 2014;Ferdows 1997aFerdows , 2006. Consequently, the relocation of certain production activities to other sites may eventually lead to the relocation of the remaining production activities to the upgraded offshore site and a loss of production capabilities at the home base, as well as a geographic separation between production and innovation activities (Slepniov, Waehrens, and Johansen 2014).…”
Section: The Lead Factory Concept and Its Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, it has been shown that subsidiaries are strategically expansive, i.e. the role of offshored sites is likely to be upgraded and could entail new capabilities (Adeyemi et al 2014;Ferdows 1997aFerdows , 2006. Consequently, the relocation of certain production activities to other sites may eventually lead to the relocation of the remaining production activities to the upgraded offshore site and a loss of production capabilities at the home base, as well as a geographic separation between production and innovation activities (Slepniov, Waehrens, and Johansen 2014).…”
Section: The Lead Factory Concept and Its Challengesmentioning
confidence: 99%
“…When increasingly more manufacturing activities, including knowledge-intensive and proprietary manufacturing tasks, can be mobile or relocated, an increasing number of countries have become viable contenders for a company's production operations and the number and significance of location decisions has increased (Porter and Rivkin 2012). As a result, subsidiaries and production plants that do not have a lead plant role in the manufacturing network have started to change their roles by increasing the scope of their activities and by seeking more autonomy in order to reduce the control of lead factories and the headquarters in their operations (Adeyemi et al 2014). If one plant changes its role in the network it will have an impact on other plants in the network (Cheng, Farooq, and Johansen 2011;) and Cheng, Farooq, and Johansen (2011) demonstrate how a plant role might evolve in a network.…”
Section: The Lead Factory Concept and Its Challengesmentioning
confidence: 99%
See 1 more Smart Citation